SISTEM PENDUKUNG KEPUTUSAN SELEKSI BEASISWA TINGKAT UNIVERSITAS MENGGUNAKAN METODE TOPSIS - Nadiya Hijriana; Erfan Karyadiputra (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2018)
One of the citizen’s rights is to get a decent education as stated in UUD 1945. The government strongly supports every citizen to get education as high as possible and giving scholarship as a program to help increase the quality of citizen’s education. Then one of problem that arise in distribution of scholarship is how to select students who is capable and apporiate to get scholarship. This research was conducted to find out the use of Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) method in scholarship selection process through Decision Support System (DSS). The result can be used as tool to support making decision for the team in University that assigned to perform the selection process. Keywords: Scholarship, Selection, Student, TOPSIS